Modulação autonômica cardíaca durante o exercício no peixe de respiração aérea bagre africano, Clarias gariepinus - Blasco, Felipe Rocco (Universidade Federal de São Carlos, 2015)
Teleost fishes were the first vertebrates to possess double autonomic innervation of the heart, where a balance between adrenergic and cholinergic actions determine heart rate (ƒH). Among teleosts, air breathing (AB) fishes are unsual because they exhibit marked changes in ƒH associated with each air-breathing event, which appear to be under autonomic control. In these species, aerobic exercise typically causes increases in air-breathing frequency (fAB), but effects of exercise on ƒH, and on the changes in ƒH with AB events, have never been studied. This was, therefore, studied in the african catfish, Clarias gariepinus, a facultative air breathing species. In particular, to investigate autonomic control of cardiac responses to exercise, and whether pharmacological abolition of ƒH control had an influence on fAB responses to exercise. Two groups of C.gariepinus were implanted with ECG electrodes under benzocaine anaesthesia, used to measure ƒH during exercise, routine between AB events, and ƒH Pre-AB and ƒH Post-AB. A peritoneal cannula was inserted to inject antagonist drugs, propranolol and atropine. In Group 1 (n = 9; 126 ± 6g EPM), animals were submitted to three sequential swimming tests at speeds of 15, 30 and 45 cm.s-1 : Control, Propranolol and Double Blockade. Group 2 (n = 9; 137 ± 8g EPM) were submitted to the same sequential swimming tests, however with a reversal in drug injections : Control, Atropine and Double Blockade. Additionally to ƒH, ƒAB and the % of adrenergic and cholinergic tones were calculated at each velocity for each test. A clear positive relation between swimming speed and ƒAB was observed. Autonomic blockade did not have major effects on these ƒAB responses. Interestingly, however, injection of propranolol alone, in group 1, caused ƒAB to be higher than control values at speeds of 30 and 45 cm.s-1, an effect that was still measured at 45 cm.s-1 after Double Blockade in that group. In group 1, the ƒH Routine of Control and Propranolol protocols showed an increase with swimming speed. However, after Double Blockade, or just atropine in Group 2, ƒH Routine was high and did not vary with swimming speed. This reveals a profound dominance of cholinergic tone on ƒH during exercise. Similarly, in group 1, the ƒH Pre- AB increased with swimming speed in Control and Propranolol tests. The ƒH Post AB was high and varied less as speed was increased in Control and Propranolol test of Group 1. Once again Double Blockade tests, or just Atropine in Group 2, abolished all changes in ƒH associated with air-breathing, at all swimming speeds, confirming a dominance of inhibitory cholinergic control of fH responses. Calculation of autonomic tones around AB events verified that adrenergic tone does not vary from Pre to Post moments, all changes in fH are due to modulation of tone action. Therefore, C.gariepinus relies on AB events to maintain aerobic metabolisn during sustained exercise. Modulation of inhibitory cholinergic tone accounts for all variations in ƒH Routine during exercise, and for all changes in ƒH during AB events. Abolition of this cholinergic control did not, however, have a major influence on AB responses to exercise.
Keywords: Peixe; Natação sustentada; Tônus adrenérgico; Frequência cardíaca; Sustained swimming; Adrenergic tone; Cholinergic tone; Heart rate; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS::FISIOLOGIA CARDIOVASCULAR